2015
DOI: 10.1074/jbc.m115.663799
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Docking Site for CD3 on the T Cell Receptor β Chain by Solution NMR

Abstract: Background: Understanding T cell signaling requires knowing the structure of the TCR-CD3 complex. Results: Solution NMR was used to identify the docking site for CD3 ectodomains on the TCR ␤ chain. Conclusion: The docking site (ϳ400 Å

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
58
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 50 publications
(72 reference statements)
10
58
4
Order By: Relevance
“…The data presented here are compatible with models in which CD3δε and CD3γε are either situated on opposite sides of the TCR (22, 46), or reside on one side of the TCR such that the subunits are ordered δ:ε:ε:γ (1, 2, 16, 17). This last model is most consistent with other experimental data, as well as recent NMR data, so we currently consider it the best approximation of the subunit organization of the TCR-CD3 complex (1, 19). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The data presented here are compatible with models in which CD3δε and CD3γε are either situated on opposite sides of the TCR (22, 46), or reside on one side of the TCR such that the subunits are ordered δ:ε:ε:γ (1, 2, 16, 17). This last model is most consistent with other experimental data, as well as recent NMR data, so we currently consider it the best approximation of the subunit organization of the TCR-CD3 complex (1, 19). …”
Section: Discussionsupporting
confidence: 83%
“…A variety of data have predicted that CD4-associated Lck and the ITAMs of the CD3 heterodimers are most closely associated upon coordinate CD4 and TCR binding to pMHC, but this prediction has not been experimentally tested (1619). The data herein provide evidence for a highly ordered, compact TCR-CD3-pMHC-CD4 macro-complex in which the cytosolic JM regions of CD4 are most closely associated with the JM regions of the CD3 heterodimers, and in particular the CD3δε subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Early NMR studies found the interaction of CD3δɛ with TCR in solution too weak to detect significant chemical shift perturbations41. More recent work found that only a mixture of CD3γɛ and CD3δɛ subunits produced detectable effects on the H3 and H4 helices of the TCR Cβ25, while a subsequent study reported weak but measurable perturbations in both Cα and Cβ upon addition of CD3δɛ or CD3γɛ, respectively26. On the cytoplasmic side, NMR studies have revealed lipid-sensitive conformational changes in the signalling domains of the CD3ζζ homodimer42 and the CD3ɛ subunit38.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect by which a reversed TCR-pMHC-I docking topology may result in poor activation of T cells centers on our understanding of the structural organization of the TCR/pMHC/co-receptor complex (Yin et al, 2012) and the CD3 docking site on TCRβ (Birnbaum et al, 2014;He et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…ITAMs (He et al, 2015;Rangarajan and Mariuzza, 2014;Yin et al, 2012). Accordingly, a reversed TCR docking polarity would place the CD3 complex outside of the arch, thereby reducing its proximity to Lck and consequently the efficiency of ITAM phosphorylation (Rangarajan and Mariuzza, 2014;Yin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%